Equazioni differenziali astratte Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Varenna (Como), Italy, May 30-June 8, 1963 - Amerio, Luigi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
T. Kato: Semi-groups and temporally inhomogeneous evolution equations.- J.L. Lions: Equations différentielles opérationnelles dans les espaces de Hilbert.- L. Nirenberg: Equazioni differenziali ordinarie negli spazi di Banach.- R.S. Phillips: Semi-groups of contraction operators.- L. Amerio: Almost-periodic equations in Hilbert spaces.- G.C. Rota: A limit theorem for the time-dependent evolution equation.- S. Zaidman: Existence and almost periodicity for some differential euqations in Hilbert spaces.
T. Kato: Semi-groups and temporally inhomogeneous evolution equations -- J.L. Lions: Equations différentielles opérationnelles dans les espaces de Hilbert -- L. Nirenberg: Equazioni differenziali ordinarie negli spazi di Banach -- R.S. Phillips: Semi-groups of contraction operators -- L. Amerio: Almost-periodic equations in Hilbert spaces -- G.C. Rota: A limit theorem for the time-dependent evolution equation -- S. Zaidman: Existence and almost periodicity for some differential euqations in Hilbert spaces.
Keywords: Partial differential equations; Partial Differential Equations